Invertebrate Abundance at Northern Bobwhite Brood Locations in the Rolling Plains of Texas - Thomas L. Warren; Sean R. Yancey; C. Brad Dabbert (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus), a bird of significant ecological and economic importance throughout the Rolling Plains region of Texas, has experienced significant population declines. Bobwhites have been the focus of extensive research for decades but little is known about foraging ecology of adults and chicks during post-hatch. Invertebrates are a key summer diet component for chicks, and supply the necessary proteins and minerals needed to fuel rapid body development. We examined brood-foraging sites to investigate invertebrate abundance. We radiomarked 121 bobwhite hens during winter-spring 2008 and 2009 and subsequently monitored 14 broods post-hatch. We collected invertebrate samples from 34 brood points and random paired-locations using sweep nets. Samples were sorted by Order to ascertain abundance and diversity. There was no difference in total abundance, abundance of Coleoptera, Hemiptera, Orthoptera, and Order diversity between brood and random locations. Northern bobwhite hens do not appear to select foraging sites based upon invertebrate abundance in the Rolling Plains of Texas.
Keywords: broods; chicks; Colinus virginianus; feeding ecology; invertebrates; northern bobwhite; Rolling Plains; Texas